PENGARUH TINGGI MUKA AIR TANAH DAN UKURAN SERAT TANAH GAMBUT TERHADAP PERAKARAN DAN PERTUMBUHAN TANAMAN AKASIA (Acacia crassicarpa) - Valentina, Risda; ', Wawan; ', Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Indonesian has the widest peat land (15 million ha) among the tropical countries, which is about 3.867.413 ha is in the Riau Province. Peat land can be usefull to make an Industry Plant Forest (IPF). The water management of the peat land is the important key of the IPF progress in the peat land to be success. The aimed of this research was to investigate the effect of the height of water level and the peat land fiber size to the root system and the growth of Acacia (Acacia crassicarpa). This research was conducted for three months at the backyard of Soil Science Laboratory of University of Riau, Pekanbaru. This study used a completely randomized design which consisted of two factors. The first factor was the peat land fiber size that has two levels, D1 (size of soft fiber) and D2 (size of hard fiber). The second factor was the the height of water level with 3 levels, which was 25 cm, 50 cm and 75 cm. This study had six combinations with 3 replicates, so that was obtained 18 unit of experiments. The data was analyzed using ANOVA and tested further by DNMRT at the 5% of significant. The observed parameter is the soil subsidence and the plant such as root weight (g), root length (cm), root volume (ml), plant height (cm), stem weight (g), plant diameter (cm), leaf weight (cm), and plant biomass (g). The result showed that the root system and the plant growth influenced by the height of water surface and the peat land fiber size. Key words: Acacia crassicarpa, peat land fiber size, growth, root system, height of water surface.